Passed with flying colours - Norhidayah, Mohamad (2018)
Kuantan, 15 march – ‘Passed with flying colours.’ Adilah A/p Adi, an Orang Asli student from SMK Lepar obtained an excellent result in Sijil Pelajaran Malaysia (SPM) 2017. She is one of the participants for Empower ECER-UMP programme.